A conceptual framework to implement gamification on online courses of computer programming learning: Implementation - Piteira, M. (2017)
On the last years, gamification has studient in variuous contexts, such as marketing, health, sports and education. According to literature, gamification integrates “elements of game design in non-game context”, with the objective of increasing users’ engagement in certain activities. Therefore gamification integration on information systems should follow a formal and clear design process. However, these gamification design processes for specific contexts are not still defined. Thus, based on a literature review the authors proposed in a previously conducted study a framework for the implementation of gamification in online courses of computer programming learning. The framework is composed of the following dimensions: target audience, general goals, learning outcomes, topics, contents, gamification, cognitive absorption, flow, and personality. In the scope of this paper, authors present and describe the implementation of the conceptual framework. In order to achive the objective, an online course of fundamentals of programming was designed and implemented, based on the previously proposed framework having then been launched a questionnaire to the students who attended the online course. The student’s attitudes towards game elements have been identified.